Pelacakan Gen Env-TM Virus Penyakit Jembrana Galur Tabanan 1995 dengan Metode Nucleic Acid Sequence Based Amplificaton - Kusumawati, Asmarani; Ratnawati, Atik; Wulandari, Ida Arlita; Hartati, Sri; Untari, Tri (Jurnal Veteriner; Vol 16 No 4 (2015), 2016)
Jembrana disease is an infectious disease in Bali cattle cause by a member of lentivirus calledjembrana disease virus (JDV). It causes an acute and severe disease syndrome with short incubationperiod. As the disease has spread to several areas in Indonesia, a simple and rapid detection method isrequired. The objective of this study to apply rapid diagnostic method for JDVTabanan 1995 strain basedon Nucleic Acid Sequence Based Amplification (NASBA) methods targeting env-tm gene. The steps of thisresearch consisted of viral RNA isolation from organ and blood of cattle experimentaly infected withJDVTabanan 1995 strain . RNA amplification was conducted by NASBA using waterbath. The NASBAproducts were then separated on 2 % agarose gel. Using this technique JDV positive result was obtainedfrom organ samples such as spleen, liver, lung, prefemoralis lymph node, prescapularis lymph node andblood generating a RNA fragment of 207 bp. In this study, diagnosis method for env tm of JDV Tabanan1995 strain can be conducted by isothermal amplification NASBA.
Keywords: Bali cattle, NASBA, env-TM gene, JDV, Tabanan 1995 strain